Etanercept Attenuates Traumatic Brain Injury in Rats by Reducing Brain TNF-α Contents and by Stimulating Newly Formed Neurogenesis. (21st April 2013) - Cheong, Chong-Un; Chang, Ching-Ping; Chao, Chien-Ming; Cheng, Bor-Chih; Yang, Chung-Zhing; Chio, Chung-Ching
Abstract : It remains unclear whether etanercept penetrates directly into the contused brain and improves the outcomes of TBI by attenuating brain contents of TNF- α and/or stimulating newly formed neurogenesis. Rats that sustained TBI are immediately treated with etanercept. Acute neurological and motor injury is assessed in all rats the day prior to and 7 days after surgery. The numbers of the colocalizations of 5-bromodeoxyuridine and doublecortin specific markers in the contused brain injury that occurred during TBI were counted by immunofluorescence staining. Enzyme immunoassay for quantitative determination of TNF- α or etanercept in brain tissues is also performed. Seven days after systemic administration of etanercept, levels of etanercept can be detected in the contused brain tissues. In addition, neurological and motor deficits, cerebral contusion, and increased brain TNF- α contents caused by TBI can be attenuated by etanercept therapy. Furthermore, the increased numbers of the colocalizations of 5-bromodeoxyuridine and doublecortin specific markers in the contused brain tissues caused by TBI can be potentiated by etanercept therapy. These findings indicate that systemically administered etanercept may penetrate directly into the contused brain tissues and may improve outcomes of TBI by reducing brain contents of TNF- α and by stimulating newly formed neurogenesis.